Fluorose dentária em crianças de seis a oito anos residentes na área de abrangência de uma unidade básica de saúde, Fortaleza-Ce : estudo de caso-controle - Teixeira, Ana Karine Macedo (2009)
The increase of dental fluorosis has been observed in fluoridated and non-fluoridated locations, suggesting the fluoride intake by others sources besides water fluoridated. The aim of this study was to investigate the dental fluorosis in children aged 6 to 8 in Fortaleza, Ceará, to identify risk and protection factors for dental fluorosis and to verify the possible associated of fluorosis with socioeconomic status. It was a case-control study realized at the health center Terezinha Parente. A total of 57 controls and 67 cases were examined by the Dean index. Data was obtained by interviewing the parents of the children, based on a structured questionnaire. Analyses of the data occurred at the Epi-Info Windows program by the Fisher test with p<0,05 and the odds ratio was calculated, with confidence interval of 95%. Statistically associated between dental fluorosis and the variable condition of live was observed (p=0,024 e OR=3,82), while no association was observed by the others socioeconomic factors. Fluoride intake by children from water, dentifrice and fluoride supplement demonstrated no significant results. But, the children who consumed powdered milk reconstituted with water before 2 years old presented 4,53 more chance to have dental fluorosis (p=0,036). And the children who have not breastfeeding presented 6,66 more chance to have fluorosis than that who breastfeeding for more than 6 mouths (p=0,007). Breastfeeding showed to be a protections factor to dental fluorosis and the consume of powdered milk reconstituted with water before 2 years old demonstrated to be risk factor in this population. It’s important to health workers recommend breastfeeding to guarantee the oral health of children.